High-temperature and long-term stability of Ho-doped potassium sodium niobate-based multifunctional ceramics. Issue 10 (15th May 2021) - Li, Wei; Hao, Jigong; Fu, Peng; Du, Juan; Li, Peng; Li, Huaiyong; Li, Wei; Yue, Zhenxing
Abstract: In this study, we synthesized lead-free 0.975(K0.4 Na0.6 )0.985 Li0.015 (Nb0.94 Sb0.06 )O3 −0.025 (Bi1− x Ho x )0.5 Na0.5 ZrO3 (KNLNS−2.5Bi1− x Ho x NZ) ceramics with excellent temperature stability and temperature-independent fatigue-free behavior. The doping with Ho 3+ ions induced the phase transition from the coexisting orthorhombic ( O ) − tetragonal ( T ) crystal phase into pure T symmetry, increasing the T:O ratio. The large-signal piezoelectric constant, d 33 *, of the synthesized KNLNS−2.5Bi1− x Ho x NZ ceramics is almost constant in the temperature range from 30 to 120 °C. In-situ dielectric permittivity measurement indicated that the O − T phase transition becomes more diffuse in the electrical field, contributing to improved thermal stability. Furthermore, the Ho-doped ceramics exhibited a fatigue-free behavior regardless of the temperature, rendering these materials promising for actuator applications. Besides, the Ho-modified ceramics showed excellent photoluminescence (PL) properties with strong green light emission upon 453 nm visible light excitation. Polarization- and temperature-induced PL quenching behaviors were observed. These changes may originate from the electric field- or temperature-induced phase transitions from the mixed O − T to pure T crystal symmetry. These excellent and reliable electrical and photoluminescent properties reflect the great potential of the synthesized ceramics for applications in multifunctional devices.